2007
DOI: 10.36366/frontiers.v15i1.217
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Global-Mindedness between Short-Term and Semester-Long Study Abroad Participants

Abstract: This article presents a study to help bolster existing study abroad research by comparing the global-mindedness of student participants at three private universities’ study abroad programs. It seeks to examine the differences between students who have participated in a short-term program, consisting of eight weeks or less and students who have participated in a semester-long program in one particular study abroad model known as an “island program.” The study also establishes the baseline levels of global- mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(78 citation statements)
references
References 13 publications
7
71
0
Order By: Relevance
“…Cohen's d calculations showed a moderate effect for each subscale and the LSE -ranging from .27 to .47 -but even effect size has been shown to fluctuate significantly by sample size (Slavin & Smith, 2009). While these results are positive, and reinforce past research suggesting that short-term programs result in measurable growth (Kehl & Morris, 2007), they should be considered preliminary at best.…”
Section: Quantitative Assessmentsupporting
confidence: 62%
“…Cohen's d calculations showed a moderate effect for each subscale and the LSE -ranging from .27 to .47 -but even effect size has been shown to fluctuate significantly by sample size (Slavin & Smith, 2009). While these results are positive, and reinforce past research suggesting that short-term programs result in measurable growth (Kehl & Morris, 2007), they should be considered preliminary at best.…”
Section: Quantitative Assessmentsupporting
confidence: 62%
“…However, numerous studies of the gender specificity of human emotions indicate greater emotionality of women compared with men, which allows us to assume their greater sensitivity to intercultural differences. This assumption is supported by the conclusions by Kehl and Morris based on the literary review: female students are more susceptible to the impact of studying abroad, as their thinking becomes more global [45]. The opposite conclusions were reached by Wang and Ching, who showed that some indicators of intercultural effectiveness ("relaxation in interaction" and "management of interaction") are higher among young men [49].…”
Section: Introductionmentioning
confidence: 87%
“…In our opinion, personality and individual determinants of ICC are less studied than socio-cultural and socio-psychological factors, especially in Russian psychology. Recently, in Western psychology, the influence of different personality traits on the ICC and related concepts has been actively studied [13,15,[43][44][45][46]. In our previous research [17][18][19][20], we mainly investigated the personality factors of the ICC, considered on the Five-Factor Model (FFM) by McCrae and Costa [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the push to internationalize higher education and produce globally competent professionals, increasing student participation in study abroad programs has become adopted widely into the mission and strategic plans of higher education institutions (ACE, 2012). In prior studies, the knowledge, skills, and abilities (KSAs) observed as outcomes among students who studied abroad included: (a) a more developed global perspective; (b) greater cultural competence skills, including cultural awareness, understanding, and sensitivity; (c) improved ability communicating and collaborating with people of cultures different than their own, (d) increased self-confidence and self-efficacy working in unfamiliar situations, (e) establishment of international networks benefitting to their careers; (f) a greater interest in pursuing an internationally focused career; and (g) continued integration of study abroad experiences into their everyday lives (Anderson, Lawton, Rexeisen, & Hubbard, 2006;Briers, Shinn, & Nguyen, 2010;Chieffo & Griffiths, 2004;Clark, Flaherty, Wright, & McMillen, 2009;Czerwionka, Artamonova, & Barbosa, 2015;Kehl & Morris, 2008;Parsons, 2010;Rowan-Kenyon & Niehaus, 2011;Sjoberg and Shabalina, 2010).…”
Section: Introductionmentioning
confidence: 99%